2021
DOI: 10.1002/jssc.202100218
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phytic acid in wheat products by complete methyl esterification and liquid chromatography‐mass spectrometry analysis

Abstract: Phytic acid, the principal storage form of phosphorus in wheat, plays both beneficial and antinutrient functions for human being, and its analytical method still needs further development. In this work, we have developed a new method for the determination of phytic acid in wheat products based on derivatization with (trimethylsilyl)diazomethane in combination with liquid chromatographymass spectrometry analysis. Methyl esterification greatly decreased the polarity and the acidity of phytic acid, and thus the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In our previous work, it was found that adding ion exchange resins could effectively remove high valent cations from solid samples, thereby signi cantly improving the extraction e ciency of anionic phytic acid. [15] This work aimed to develop an e cient and rapid method for the determination of PFAAs in soil by chelating resin-assisted extraction.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, it was found that adding ion exchange resins could effectively remove high valent cations from solid samples, thereby signi cantly improving the extraction e ciency of anionic phytic acid. [15] This work aimed to develop an e cient and rapid method for the determination of PFAAs in soil by chelating resin-assisted extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the measurement of PA in food is necessary. Liquid chromatography 5,6 and spectroscopy 7,8 are current methods for PA analysis that have some disadvantages such as being timeconsuming, expensive, and complex. Thus, we have selected the simple and low-cost electrochemical method.…”
Section: Introductionmentioning
confidence: 99%